The relationship between exercise participation satisfaction, exercise commitment, and exercise adherence intention according to peer relationships among Korean school sports club participants - Jung, Tae Gyeom; Jung, Myung Kyu; Lee, Ji Hae; Kim, Min Jun (Frontiers in Psychology, 2025)
IntroductionThis study investigated the structural relationships among peer relationships, exercise participation satisfaction, exercise commitment, and exercise adherence intention in the context of Korean adolescents participating in school sports clubs. The aim was to provide empirical insights that can inform strategies to promote sustained participation in physical activity.MethodsThis study collected data from 245 middle school students in South Korea who were either currently participating in or had previous experience with school sports clubs, using a snowball sampling method. The data collection process was conducted with prior approval from the Institutional Review Board (IRB), and informed consent was obtained from both the participants and their legal guardians. The collected data were analyzed using frequency analysis, descriptive statistics, confirmatory factor analysis (CFA), reliability analysis, correlation analysis, and structural equation modeling (SEM).ResultsThe results indicated that peer relationships, exercise participation satisfaction, and exercise commitment significantly influenced exercise adherence intention. Peer relationships had a direct effect on both exercise participation satisfaction and exercise commitment, and an indirect effect on exercise adherence intention through these mediating variables.DiscussionThese findings highlight the importance of developing intervention strategies that foster positive emotional experiences—particularly satisfaction and commitment—arising from peer relationships. Such strategies may be critical for encouraging long-term engagement in school-based sports programs among adolescents.